A Greek state in formation : the origins of civilization in Mycenaean Pylos - Davis, Jack L. (Sather classical lectures, 2021)
"The Mycenaean civilization of the Greek Bronze Age was identified 150 years ago, yet its origins remain obscure. Jack L. Davis, codirector of ongoing excavations at the Palace of Nestor at Pylos takes readers on a tour of the beginnings of Mycenaean civilization through a case study of this important site. In collaboration with Sharon R. Stocker, Davis demonstrates that this ancient place was a major node for the exchange of ideas between the already established Minoan civilization, centered on the island of Crete, and the Greek mainland. Davis and Stocker show how this adoption of Minoan culture created an ideology of power focused on a single individual, one that celebrated his military prowess and invested him with divine authority--a figure instantly recognizable to readers of Homer and students of Greek history. A Greek State in Formation makes the powerful case that a knowledge of the Greek Bronze Age is indispensable to the Classics curriculum"--